2018
DOI: 10.1074/jbc.ra117.001299
|View full text |Cite
|
Sign up to set email alerts
|

TGFβ and IGF1R signaling activates protein kinase A through differential regulation of ezrin phosphorylation in colon cancer cells

Abstract: Aberrant cell survival plays a critical role in cancer progression and metastasis. We have previously shown that ezrin, a cAMP-dependent A-kinase anchoring protein (AKAP), is upregulated in colorectal cancer (CRC) liver metastasis. Phosphorylation of ezrin at threonine 567(T567) activates ezrin and plays an important role in CRC cell survival associated with XIAP and survivin upregulation. In this study, we demonstrate that, in FET and GEO colon cancer cells, knockdown of ezrin expression or inhibition of ezri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 56 publications
0
21
0
Order By: Relevance
“…Insulin‐like growth factor 1 receptor (IGF1R) signaling has been shown to be upregulated in many cancers including CRC, and approximately 30% to 40% of all CRCs are IGF1R‐dependent . IGF1R signaling has been shown to play a critical role in CRC cell survival . Recent in vitro and in vivo studies by our group demonstrated that inhibition of IGF1R signaling induces apoptosis, in association with downregulation of XIAP and survivin, while activation of IGF1R by transferrin and insulin (TI) increases CRC cell survival .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Insulin‐like growth factor 1 receptor (IGF1R) signaling has been shown to be upregulated in many cancers including CRC, and approximately 30% to 40% of all CRCs are IGF1R‐dependent . IGF1R signaling has been shown to play a critical role in CRC cell survival . Recent in vitro and in vivo studies by our group demonstrated that inhibition of IGF1R signaling induces apoptosis, in association with downregulation of XIAP and survivin, while activation of IGF1R by transferrin and insulin (TI) increases CRC cell survival .…”
Section: Resultsmentioning
confidence: 99%
“…IGF1R signaling has been shown to play a critical role in CRC cell survival . Recent in vitro and in vivo studies by our group demonstrated that inhibition of IGF1R signaling induces apoptosis, in association with downregulation of XIAP and survivin, while activation of IGF1R by transferrin and insulin (TI) increases CRC cell survival . Since GEO and CBS CRC cells are dependent on IGF1R signaling for survival, we hypothesized that inhibition of the IGF1R pathway would affect NHERF1‐mediated CRC cell survival.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cyclic-AMP-dependent protein kinase A-anchoring proteins (AKAPs) structurally interacted with PKA and targeted these supra-molecular complexes to particular subcellularly localized regions where they phosphorylated different proteins. Ezrin inhibition mediated activation of PKA was found to be dependent on AKAP149 in colorectal cancer cells [70].…”
Section: Smad Proteins As Tumor Suppressorsmentioning
confidence: 98%
“…TGFβ inhibited ezrin phosphorylation at 567 th threonine residue which resulted in protein kinase-A (PKA) activation and apoptosis. TGFβ1 treatment time-dependently decreased ezrin phosphorylation [70]. Cyclic-AMP-dependent protein kinase A-anchoring proteins (AKAPs) structurally interacted with PKA and targeted these supra-molecular complexes to particular subcellularly localized regions where they phosphorylated different proteins.…”
Section: Smad Proteins As Tumor Suppressorsmentioning
confidence: 99%